A complex case of eosinophilic pleural effusion: an unconventional response to anti-tubercular therapy - Ankit, Grover (International Journal of Research in Medical Sciences, 2023)
Eosinophilic tuberculosis (TB) is a rare form of TB characterized by the presence of eosinophils in pleural fluid. It remains an uncommon presentation and often poses a diagnostic challenge due to its resemblance to other conditions with eosinophilic pleural effusions. Here, we present a detailed case report of a 26-year-old female who presented with a two-week history of on-and-off fever, non-productive cough, and exertional dyspnea. Physical examination revealed absent air entry in the left infra-scapular and intra-axillary areas. Routine investigations and chest X-ray indicated a moderate left-sided pleural effusion with peripheral eosinophilia. Liver and kidney function tests were within the normal range. A left pleural tap was performed, and the pleural fluid analysis demonstrated an exudative effusion with predominantly eosinophils. Additional investigations, including ADA levels, Genexpert for TB, TB PCR, C-ANCA, P-ANCA, and total IgE levels, were performed to rule out other possible causes of eosinophilia, but the results were all negative or normal. No growth was observed on culture. Based on clinical history, examination findings, and investigation results, a diagnosis of eosinophilic TB was considered. The patient was started on empirical anti-tubercular drugs, which led to a favorable response and near-complete resolution of pleural effusion after 6 weeks of treatment. Regular follow-up and monitoring were conducted, and the patient completed a 6-month course of anti-tubercular treatment. This case report highlights the importance of considering eosinophilic TB in the differential diagnosis of pleural effusions, especially in young patients with no history of allergies or other underlying conditions.